Antibiotic Resistance: A Concern to Veterinary and Human Medicine - Aryal, Sitaram (Nepal Agriculture Research Journal, 2011)
Bacterial resistance to antibiotics occurs even without the use of antibiotics. Antibiotic use exerts a selective pressure to the bacterial flora that help in the emergence and development of antibiotic resistance. Antibiotics are used worldwide both in veterinary and human medicine. The wide spread use of antibiotics in human and animal has raised the concern about the development of resistant and multi resistant bacteria that possess a potential danger to animals and men, as resistance may cause treatment failure. Resistance may be natural or acquired. Acquired resistance is due to transfer of extrachromosomal genetic material (R-plasmids) and is very important. The R-plasmids are spread to other bacterial cells by transformation, transduction, conjugation and transposition. Transmitted antibiotic resistance in disease causing bacteria may cause zoonotic infections and resistant non-infectious bacteria may serve as a reservoir of R- plasmids for the pathogenic organism(s). This paper highlights the mechanism of development of resistance in bacteria and means to minimize it. Key words: Antibiotic resistance; Bacteria; Extrachromosomal material; Resistance; R-plasmids DOI: http://dx.doi.org/10.3126/narj.v4i0.4873 Nepal Agriculture Research Journal Vol. 4&5, 2001/2002 Page: 66-70 Uploaded date: 9 June, 2011